Secondary school students' experience of young adult literature - Govindarajoo, Mallika Vasugi (2014)
Although the characteristics of Young Adult Literature (YAL) relate closely to the issues faced in young adulthood, in Malaysia, where the history of literature learning is still relatively new, the potential of YAL as selected reading material for students in national secondary schools has not yet been given enough consideration. Texts that were used in the newly introduced literature component of the English language in Malaysian secondary schools in 2000 were in fact found to have little relevance or interest to the young adult student. To address this, the texts for the 2nd cycle of the literature component beginning 2010 were projected by the Malaysian Ministry of Education to focus on teenage issues, which is indicative of YAL. However research of an inductive and reflective nature to describe the Malaysian young adult student‘s experience of YAL has been up to the moment insufficient. The aim of this study which is reflected in the two research questions were firstly to determine the extent to which the new texts belonged to the genre of YAL and secondly the extent to which they were relevant to the young adult Malaysian student. Sub-questions were guided by the defining criteria of YAL and because the study required in-depth knowledge of young adult students‘ essence of experience‘ and engagement with the texts, the method used was phenomenological. The sampling for the study was purposeful and participants were eight students from the fourth form in a Malaysian national secondary school. Data for the study came from participants‘ written journal reflections during the reading of the three novels prescribed by the Malaysian Ministry of Education; (Step by Wicked Step by Anne Fine, Catch Us If You Can by Katherine McPhail and The Curse by Lee Su Ann) and from follow-up qualitative interviews. Data analysis in this study included the transcribing and reading of the reflective journals and interviews. The findings from the study revealed that the presence of YAL elements especially teenage issues was limited in all three novels .Thus the objective of relevance to the young adult Malaysian student as projected by the text selection committee was only partially fulfilled. With the exception of Step by Wicked Step, the ages of the protagonists in the novels were on the boundaries rather than the middle range of young adulthood. Descriptions of the young adult protagonists‘ appearance, speech and mannerisms were found to be minimal and there was little reference to the development of sexual identity and body image. Themes were related to YAL but there were significant differences in terms of believability, portrayal of characters and sense of closure. In terms of identity and relevance of novels to the young adult participant, the findings revealed that despite the limited presence of young adult issues, participants strove to identify and connect with any parts of the novels that paralleled familiar situations in their lives. A sense of reciprocity, bonding or mediatory role developed at times between participant and characters. The identification of participant with familiar issues and characters were significant not only by their presence but also by their absence. Expectations of participants towards adult characters were higher and attitudes tended to be more judgmental and less forgiving compared to young adult protagonists. Participants‘ responses also indicated the need for literary texts to provide a realistic portrayal of society. The study provides valuable information on how young adult students identify with issues and characters that are relevant to them and thus points towards the need for a more definite inclusion of YAL when selection of literary texts for young adults needs to be made.